The effects of wearable resistance training on metabolic, kinematic and kinetic variables during walking, running, sprint running and jumping: A systematic review - Macadam, P.; Cronin, J. B.; Simperingham, K. D. (Sports Medicine, 2017)
Wearable resistance training (WRT) provides a means of activity- or movement-specific overloading, supposedly resulting in better transference to dynamic sporting performance. Objective: The purpose of this review was to quantify the acute and longitudinal metabolic, kinematic and/or kinetic changes that occur with WRT during walking, running, sprint running or jumping movements. Data Sources: PubMed, SPORTDiscus, Web of Science and MEDLINE (EBSCO) were searched using the Boolean phrases (limb OR vest OR trunk) AND (walk* OR run* OR sprint* OR jump* OR bound*) AND (metabolic OR kinetic OR kinematic) AND (load*). Study Selection: A systematic approach was used to evaluate 1185 articles. Articles with injury-free subjects of any age, sex or activity level were included. Results: Thirty-two studies met the inclusion criteria and were retained for analysis. Acute trunk loading reduced velocity during treadmill sprint running, but only significantly when loads of 11 % body mass (BM) or greater were used, while over-the-ground sprint running times were significantly reduced with all loads (8-20 %BM). Longitudinal trunk loading significantly increased jump performance with all loads (7-30 %BM), but did not significantly improve sprint running performance. Acute limb loading significantly increased maximum oxygen consumption and energy cost with all loads (0.3-8.5 %BM) in walking and running, while significantly reducing velocity during sprint running. Limitations: The variation in load magnitude, load orientation, subjects, testing methods and study duration no doubt impact the changes in the variables examined and hence make definitive conclusions problematic. Conclusions: WRT provides a novel training method with potential to improve sporting performance; however, research in this area is still clearly in its infancy, with future research required into the optimum load placement, orientation and magnitude required for adaptation.